2006
DOI: 10.1016/j.socscimed.2005.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Time in the United States, social support and health behaviors during pregnancy among women of Mexican descent

Abstract: Among women of Mexican descent, increased acculturation in the United States has been associated with poorer health behaviors during pregnancy. This study examined a population of low-income women of Mexican descent in an agricultural community to determine whether social support patterns were associated with age at arrival in the U.S.; whether social support was associated with pregnancy behaviors; and whether increased social support could prevent some of the negative pregnancy behaviors that accompany accul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
1
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 50 publications
5
114
1
7
Order By: Relevance
“…Stepwise regression indicated that 19.3% of the variability in length of gestation could be accounted for by the sense of belonging (Table 5). This is dissimilar to Harley and Eskenazi (2006) who examined the effect of social support and health behaviors during pregnancy among 568 women of Mexican descent and found that "social support was lowest among recent Mexican immigrants and highest among women who had lived their entire lives in the United States" (p. 3055). This current finding may be due to the social context in which the subjects live.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Stepwise regression indicated that 19.3% of the variability in length of gestation could be accounted for by the sense of belonging (Table 5). This is dissimilar to Harley and Eskenazi (2006) who examined the effect of social support and health behaviors during pregnancy among 568 women of Mexican descent and found that "social support was lowest among recent Mexican immigrants and highest among women who had lived their entire lives in the United States" (p. 3055). This current finding may be due to the social context in which the subjects live.…”
Section: Discussioncontrasting
confidence: 64%
“…This early finding was further validated by Campos, Dunkel Shetter, Adbou, Hobel, Glynn and Sandman (2008). Among Latinas, social support during pregnancy is often provided by the maternal grandmother with additional support from the father of the baby and a network of immediate family and friends (Harley & Eskenazi, 2006;Thornton et al, 2006). Landale, Oropesa, Ilanes and Gorman (1999) found that Puerto Rican women who lived with the baby's father throughout the pregnancy reported lower levels of stress than women who did not.…”
Section: Stress Buffers and Pregnancymentioning
confidence: 99%
“…As found in other studies, churches played a crucial role in providing emotional, instrumental and informational support to the participants in preparation for childbirth (Harley and Eskenazi 2006). The participants-particularly Ayanda, Maria, Kudzai and Fatima-acknowledged going to church and receiving prayers, advice and exercises during pregnancy.…”
Section: Religion and Church As Supportmentioning
confidence: 53%
“…This consistency between the four measures of acculturation is reassuring, both from the internal consistency standpoint (all trends were in the same direction) and for external comparison purposes (as compared with other studies that may have only analyzed one or two acculturation measures). 31,45,46 Among the 1024 women who delivered term and normal birth weight infants in our study, we found the largest variation in adjusted mean scores for the patient-centered decision making domain (scores ranged from 3.62 among more acculturated women to 4.10 among less acculturated women) and also varied substantially by type of health insurance (scores ranged from 3.07 among privately insured women to 4.36 among uninsured women). This variation in scores may reflect underlying differences in expectation or preferences, with higher expectations for patient-centered decision making among US-born and privately insured women than among less acculturated and publicly insured women.…”
Section: Discussionmentioning
confidence: 65%